Handbook of thermoluminescence - Furetta, C (World Scientific Pub, 2003)
Includes bibliographical references and index.; This book provides practical support for research, study, routine work and terminology in the field of thermoluminescence (TL). It discusses the methods of determining the kinetic parameters, the procedures for characterizing a thermoluminescent dosimetric system, and the definition of terms commonly used in the literature. Furthermore, the analytical treatments of the various TL models are fully developed. The arguments are given in alphabetical order to ease research